The Participation of Youth of Western Countries in Political Life of the Society. The Youth in the Political Life of the Society - PELEVIN, Sergei; TAUBAEV, Baktibek; TILEUBERGENOV, Yerazak; VASILIEV, Aleksei (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018DO - 10.14505//jarle.v9 2(32).38, 2018)
The purpose of the article is to consider the involvement of foreign youth in political life. The article uses the method of comparison and concretization. The civil involvement is considered as a part of the growing-up and personality development of young people: awareness of personal identity, tolerance and other important aspects. The supporters of this approach regard the assistance to young people as individuals with a wide range of opportunities and the right of choice as the best strategy. The society becomes more and more globalized and differentiated, thus, showing fewer consensuses between norms and values that can provoke conflicts between youth and surrounding reality. In such a situation, it is more important to concentrate on the search of ways for youth to understand the essence of politics and to find a place in it as political agents rather than on deepening formal knowledge about political system. The research findings can be used in political science classes at universities.